Analysis Of The Performance Of The Cipager Dam Irrigation Network: Case Study Cipager Dam, Cirebon Regency, Indonesia - Dhymas Eka Priyananda; Gagam Fratama Putra; Regal Julian Wiguna; Awliya Thribhuwana (Riviera Publishing, 2025)
The Cipager Dam, located in Cirebon Regency, Indonesia, serves as a crucial infrastructure for irrigation in the region, with an irrigation network covering over 1,600 hectares. Despite its importance, the dam faces issues related to maintenance, network conditions, and workforce shortages, affecting its performance and water distribution efficiency. This study aims to evaluate the performance of the Cipager Dam irrigation network by analyzing the condition of the main and secondary channels, assessing water availability against demand, and exploring the impact of operational deficiencies. The research adopts a descriptive-inductive approach using both primary and secondary data. Primary data were collected through direct field observation of the irrigation infrastructure, while secondary data were obtained from institutional records, rainfall data, and historical irrigation performance. The study found that the water discharge from Cipager River is adequate to meet irrigation needs. However, the irrigation network suffers from moderate to severe damage, and there is a shortage of management personnel. The operational and maintenance budget remains insufficient despite a slight increase in 2025. The study suggests that improving the irrigation network’s maintenance, integrating advanced technologies like IoT, and enhancing workforce management could significantly improve the system's performance and sustainability. Future studies should explore these areas and compare other irrigation systems in Indonesia to identify best practices.